ANALYSIS OF PSAK 71 IMPLEMENTATION ON ALLOWANCE FOR IMPAIRMENT OF FINANCIAL ASSETS - Kartika Kartika; Andriana Andriana; Alfi Arif; Sudarno Sudarno; Hendrawan Santosa Putra (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
Banking is one of the main industries that can be used as an indicator of the economy in a country. The health condition of a country's economy can be assessed through the level of soundness and financial performance of its banking industry. In 2017 the Financial Accounting Standards Board (DSAK) together with IAI, ratified a new PSAK (Statement of Financial Accounting Standards), namely PSAK 71 regarding Financial Instruments guided by IFRS 9. The update to PSAK 71 is a response to companies, especially those engaged in financial or financial to risky credit. This study aims to determine the results of the comparative analysis of financial performance before and after the application of PSAK 71 on Allowance for Impairment Losses in Banking by using a case study at Bank Rakyat Indonesia. The analytical method used in this study is the CAMEL method. The results of the calculation of financial ratio analysis using the CAMEL method can be seen that the overall financial performance of BRI before and after the implementation of PSAK 71 experienced significant changes, both in terms of capital, earning assets, management, profitability and liquidity.